Implementasi Random Forest dengan LASSO dalam Klasifikasi Penyakit yang Ditularkan Melalui Nyamuk - Pradyto, Kadek Dwitya Adhi; Raharja, Made Agung (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023DO - 10.24843/JNATIA.2023.v01.i04.p23, 2023)
Several diseases that can attack human health can be transmitted through disease vectors. One of the insects belonging to the disease vector is the mosquito. Diseases that can attack humans due  to  transmission  through  mosquitoes  include  malaria,  dengue  fever,  chikungunya,  yellow fever, rift valley fever, and many more. With so many types of diseases that are transmitted by mosquitoes  and  the  symptoms  that  look  quite  similar,  a  classification  process  is  carried  out  to distinguish  the  types  of  diseases.  In  this  study,  the  classification  was  carried  out  using  the Random Forest algorithm withthe LASSO algorithm for feature selection. It was found that the average accuracy values of the Random Forest before and  after  carrying  out feature selection using LASSO were 88% and 76%, respectively. From the values obtained, it can be concluded that  the  Random  Forest  has  better  performance  without  feature  selection  using  the  LASSO method.